Vector - Electrocardiography in proven cases of congenital cardiography - Eyzaguirre R., Guillermo A. (1964)
1. a) Vector and have presented 35 cases of heart disease Electrocardiographically s Congenital all of which have had surgical confirmation . They are: Septal , 20 cases ; Persistence Atrioventricular Canal , 6 cases ; Pulmonary stenosis , 5 cases and Tetralogy of Fallot, 4 cases. b ) the amendments to suffer Eccr are discussed. ys VCG regarding assessment and postoperative evolution . Two . a) The E.c.g. Communication ostium secundum atrial showed no significant findings out of right ventricular hypertrophy and pattern rsR ' in precordial V1. b ) the correlation of " crochetage " QRS was shown with its counterpart in the vectorcardiogram in cases of septal defect secundum . c ) electrocardiographic findings A QRS deflection to the left , first-degree block and RSR pattern in the precordial lead V1 in cases of persistent common atrioventricular canal are described. d ) the VCG s is described , where Atrio - Ventricular Canal Joint and noting the value of vectorcardiogram and electro as methods not only for diagnosis but for ASDs : differentiation between types Ostium Primum and Secundum . Three . a) the deviation of the electrical axis to the right, the orientation vector s E QRS in severe right ventricular hypertrophy and ET ​​s mismatch in Pulmonary stenosis is discussed. April . a) A typical QRS and AT Tetralogy of Fallot and its three-dimensional orientations is described. The Rs complex in V1 with meaning of " systemic right ventricle ." b ) electrocardiographic - hemodynamic correlation is discussed. c ) the Vectorcardiogram is described in Tetralogy of Fallot as a predominance of classical anterior and inferiorly directed electric forces and right . May . On a three-dimensional diagram that can be mounted on the electrostatic and vectorcardiogramas so that the student can read and interpret the electromotive forces is proposed.